Revolutionary womanhood : feminisms, modernity, and the state in Nasser's Egypt - Bier, Laura (Stanford studies in Middle Eastern and Islamic societies and cultures., 2011)
"The first major historical account of gender politics during the Nasser era, Revolutionary Womanhood analyzes feminism as a system of ideas and political practices, international in origin but local in iteration. Drawing connections between the secular nationalist projects that emerged in the 1950s and the gender politics of Islamism today, Laura Bier reveals how discussions about education, companionate marriage, and enlightened motherhood, as well as veiling, work, and other means of claiming public space created opportunities to reconsider the relationship between modernity, state feminism"--Provided by publisher.